Hemodynamic Retinal Artery Occlusion with Ipsilateral Carotid Artery Occlusion - Hwang, Jiunn-Feng; Chen, Yu; Chen, San-Ni (Archives of Clinical and Medical Case Reports, 2022)
Retinal artery occlusion (RAO) with hemodynamic changes including ipsilateral carotid stenosis/occlusion, reduced blood flow, and responsive compensatory flow, is considered as hemodynamic RAO. Multiple emboli are highly associated with hemodynamic RAO that embolism may raise from turbulence of stenotic carotid artery or accompany with compensatory flow via the collaterals. With compensatory flow, most hemodynamic RAO are transient and may have fair visual outcome. In this hemodynamic RAO, severe ischemic macular edema and devastating visual outcome is a result of multiple mechanisms. Ipsilateral ICA occlusion with decreased blood flow, inadequate primary compensatory flow to the eye, elongated duration of an alternative compensatory flow to re-establish ophthalmic circulations, and terminal infarctions of multiple emboli may all contribute the irreversible retinal damage and poor vision.